Media Sosial Sebagai Sarana Peningkatan Literasi Digital Masyarakat - Bagus Fadlan Aulia; Salwa Shofiyah Subarjah; Yulia Rahma (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Social media has become an integral part of Indonesian life. Platforms like Facebook, Instagram, Twitter and TikTok have revolutionized the way we communicate, consume information and do business. The impact of social media on Indonesian society is complex and varied, some positive and some negative. In Indonesia, social media has also become one of the alternatives to improve public literacy, as Indonesians prefer to read using gadgets, especially videos and interesting posts. The research method we use is qualitative, and the author understands the importance of phenomena that occur in Indonesia in relation to the impact of social media on Indonesian society, especially the advantages and disadvantages of increasing Masa literacy. The author compiled this article by analyzing various sources of information regarding the influence of social media. These are the main sources of information that the author consulted when writing this article. Furthermore, the author's environment was analyzed from the point of view of the influence of social media. The purpose of publishing this article is to inform readers that social media can be a medium to improve literacy in Indonesia. Furthermore, readers can find out Indonesia's literacy rate at the global level, which indicates that Indonesia is still among the countries with the lowest literacy rate globally.